Nudging farmers toward disease-free shrimp technology with financial incentives: Experimental evidence from Bangladesh - Bin Khaled, Muhammad Nahian; Maredia, Mywish K.; Narayanan, Sudha; Belton, Ben; Kabir, Razin (International Food Policy Research Institute, 2025)
Price discounts are a common policy tool to promote agricultural technology adoption in low-income settings, yet their effectiveness may be limited when farmers face uncertainty or have access to familiar alternatives. We test this through a randomized controlled trial with shrimp farmers in southwestern coastal Bangladesh, a region highly exposed to climate shocks. The government promotes Specific Pathogen Free (SPF) post-larvae (PL)—certified as disease-free—to reduce high mortality in shrimp farming. Farmers were randomly offered varying discount levels for two SPF-PL types, differing in size uniformity and market price (proxies for quality), with the highest discount reducing their prices to parity with conventional non-SPF PL. We find no significant effect of discounts on adoption of the lower-priced Mid-grade SPF-PL, characterized by less size uniformity. In contrast, discounts significantly increased adoption of the higher-priced, more uniform Premium-grade SPF-PL, raising uptake by 10–19 percentage points among active shrimp farmers. Larger discounts did not yield higher adoption than smaller ones, indicating diminishing returns to discount generosity. Heterogeneity analyses reveal behavioral and contextual mechanisms: prior exposure to Mid-grade SPF-PL reduced its subsequent adoption but increased responsiveness to Premium-grade, consistent with experience effects and reference dependence. Cyclone exposure dampened treatment responses, suggesting capital constraints, while infrastructure preparedness (e.g., nursing facilities) enhanced uptake. These findings underscore that in high-risk agricultural systems, price incentives alone may not drive adoption unless the promoted input is perceived as effective. Successful promotion strategies must integrate quality assurance with attention to farmer experience, behavioral biases, and vulnerability to shocks.